Mary's bodily Assumption - Levering, Matthew, 1971- (University of Notre Dame Press, 2015)
In Mary's Bodily Assumption, Matthew Levering presents a contemporary explanation and defense of the Catholic doctrine of Mary's bodily Assumption.